Purify and destroy : the political uses of massacre and genocide - Sémelin, Jacques (CERI series in comparative politics and international studies., 2007)
"Purify and Destroy demonstrates that it is indeed possible to compare the Holocaust, the Rwandan genocide, and ethnic cleansing in Bosnia Herzegovina while respecting the specificities of each of these appalling phenomena." "Based on seminal distinction between massacre and genocide, Purify and Destroy identifies the main steps of a general process of destruction, both rational and irrational, born of what Semelin terms "delusional rationality." Semelin identifies the main stages that can lead to a genocidal process, and explains how ordinary people can become perpetrators."--Jacket